Determination of antibiotic residues in muscle, liver and kidney of guinea pigs marketed in four cities of Peru - Ampuero-Riega, Juana (2021)
The aim of this study was to determine the presence of antibiotics in the liver, kidney and muscle of guinea pigs of intensive breeding in four cities of Peru. For this, 410 carcass samples (liver, kidney and muscle) were evaluated. The samples were taken during the air-drying stage ready for sale and sent to the laboratory at 4 °C. The technique used was the microbiological agar diffusion with the Bacillus subtilis ATCC 6633 strain as the sensitive strain and a commercial enrofloxacin 5 µg disc as a positive control. The plates were incubated at 37 °C for 24 hours and then the diameter of the zones of inhibition of bacterial growth was measured with the Kirby-Bauer ruler. Frequencies of bacterial growth inhibition halos of 28.54 + 4.37% (117/410) were obtained in kidney samples, 27.07 + 4.3% (111/410) in muscle, and 26.59 + 4.28% (109/410) in liver. The study shows a high frequency of antibiotics in muscle, liver and kidney of guinea pig carcass on sale for human consumption in three of four cities in Peru.